Expression of RNase P RNA in Saccharomyces cerevisiae is controlled by an unusual RNA polymerase III promoter. - Lee, J Y (1991)
The RNA subunit of Saccharomyces cerevisiae nuclear RNase P is encoded by a single-copy, essential gene, RPR1. The 369-nucleotide mature form of the RNA has an apparent precursor with an 84-nucleotide 5' leader and approximately 33 nucleotides of additional 3' sequence. Analysis of RPR1 transcription in a strain with a temperature-sensitive lesion in RNA polymerase III shows that the gene is transcribed in vivo by RNA polymerase III. Examination of potential promoter regions using both progressive upstream deletions and point mutations indicates that at least two sequences contained within the 5' leader region are essential for expression in vivo, while sequences farther upstream influence efficiency. The required leader elements resemble tRNA gene-like A-box and B-box internal promoters in sequence and spacing. As in the tRNA genes, transcription factor TFIIIC binds to this region in vitro and binding is severely reduced by either A-box or B-box point mutations that impair expression in vivo. It thus appears that the yeast RNase P RNA gene has adopted a promoter strategy that places an RNA polymerase III "internal" promoter upstream of the mature structural domain to help drive transcription.